Characterization of disease-propagating stem cells responsible for myeloproliferative neoplasm–blast phase - Xiaoli Wang; Raajit K. Rampal; Cing Siang Hu; Joseph Tripodi; Noushin Farnoud; Bruce Petersen; Michael R. Rossi; Minal Patel; Erin McGovern; Vesna Najfeld; Camelia Iancu-Rubin; Min Lu; et al. (JCI Insight, 2022)
Chronic myeloproliferative neoplasms (MPN) frequently evolve to a blast phase (BP) that is almost uniformly resistant to induction chemotherapy or hypomethylating agents. We explored the functional properties, genomic architecture, and cell of origin of MPN-BP initiating cells (IC) using a serial NSG mouse xenograft transplantation model. Transplantation of peripheral blood mononuclear cells (MNC) from 7 of 18 patients resulted in a high degree of leukemic cell chimerism and recreated clinical characteristics of human MPN-BP. The function of MPN-BP ICs was not dependent on the presence of JAK2V617F, a driver mutation associated with the initial underlying MPN. By contrast, multiple MPN-BP IC subclones coexisted within MPN-BP MNCs characterized by different myeloid malignancy gene mutations and cytogenetic abnormalities. MPN-BP ICs in 4 patients exhibited extensive proliferative and self-renewal capacity, as demonstrated by their ability to recapitulate human MPN-BP in serial recipients. These MPN-BP IC subclones underwent extensive continuous clonal competition within individual xenografts and across multiple generations, and their subclonal dynamics were consistent with functional evolution of MPN-BP IC. Finally, we show that MPN-BP ICs originate from not only phenotypically identified hematopoietic stem cells, but also lymphoid-myeloid progenitor cells, which were each characterized by differences in MPN-BP initiating activity and self-renewal capacity.